2021
DOI: 10.1177/11206721211000647
|View full text |Cite
|
Sign up to set email alerts
|

Methylenetetrahydrofolate reductase polymorphisms as risk factors for retinal venous occlusive disease: A literature review

Abstract: The role of polymorphisms of methylenetetrahydrofolate reductase (MTHFR) gene in retinal vein occlusion (RVO) is a theme of discussion since the first reports of RVO in patients with MTHFR C677T mutation and without classic acquired risk factors for retinal vascular disease. The association between MTHFR polymorphisms and RVO has been studied over the last 20 years producing conflicting results. This review aims to summarize the literature concerning the role MTHFR polymorphisms as risk factors for RVO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Many studies have shown that diabetes is associated with microvascular disease and RVO. 19 , 21 , 22 , 24 , 31 , 37 , 39 , 42 , 55 Vitamin D deficiency, although widespread in the general population, is more frequent and problematic for patients with any of the aforementioned risk factors. Severity of disease manifestation appears to be proportional to the degree of vitamin D deficiency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have shown that diabetes is associated with microvascular disease and RVO. 19 , 21 , 22 , 24 , 31 , 37 , 39 , 42 , 55 Vitamin D deficiency, although widespread in the general population, is more frequent and problematic for patients with any of the aforementioned risk factors. Severity of disease manifestation appears to be proportional to the degree of vitamin D deficiency.…”
Section: Discussionmentioning
confidence: 99%
“… 23 , 28 36 Atherosclerosis, autoimmune disease, diabetes, dyslipidemia, glaucoma, HTN, hyperviscosity, obesity, smoking, and thrombotic syndromes (antiphospholipid syndrome, antithrombin deficiency, factor 5 Leiden mutations, hyperhomocysteinemia, protein C and S deficiency, and prothrombin gene mutations) are familiar modifiable risk factors for RVO/CRVO. 19 , 21 22 , 24 , 37 40 Overall, a best practices protocol should be developed and become the standard of care for ophthalmologists as well as other practitioners managing vascular disease.…”
Section: Introductionmentioning
confidence: 99%
“…Mutations in the MTHFR gene affect the activity of the enzyme, leading to elevated homocysteine levels. Common mutations include C677T and A1298C [11].…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in the MTHFR gene affect the activity of the enzyme, leading to elevated homocysteine levels. Common mutations include C677T and A1298C [ 11 ]. Double heterozygous refers to patients who have heterozygous mutations for both of these mutations [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, in our case, although the MTHFR heterozygous mutation was present, homocysteine levels were within the normal range, and therefore primary thrombophilia was not considered. Although there is evidence in the literature that hyperhomocysteinemia increases the risk of retinal vein occlusion, no relationship has been found between the MTHFR C677T polymorphism and retinal vein occlusion [ 11 , 12 ]. However, this is still a controversial topic.…”
Section: Discussionmentioning
confidence: 99%